2012
DOI: 10.1111/j.1742-4658.2012.08567.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of H3K4me3 demethylation by KDM5B/Jarid1B/PLU1 reveals strong substrate recognition in vitro and identifies 2,4‐pyridine‐dicarboxylic acid as an in vitro and in cell inhibitor

Abstract: Dynamic methylations and demethylations of histone lysine residues are important for gene regulation and are facilitated by histone methyltransferases and histone demethylases (HDMs). KDM5B ⁄ Jarid1B ⁄ PLU1 is an H3K4me3 ⁄ me2-specific lysine demethylase belonging to the JmjC domaincontaining family of histone demethylases (JHDMs). Several studies have linked KDM5B to breast, prostate and skin cancer, highlighting its potential as a drug target. However, most inhibitor studies have focused on other JHDMs, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 38 publications
6
55
0
Order By: Relevance
“…8A). Two studies have identified 2,4-pyridine-dicarboxylic acid (PDCA) as a small-molecule inhibitor of KDM5B (53,54). Following 24 h of OSKM overexpression, we observed a higher density and compaction of shKdm5b 4TF-MEFs than shLuc 4TF-MEFs (Fig.…”
Section: Kdm5b-depleted Es Cells Exhibit Reduced Self-renewalmentioning
confidence: 59%
“…8A). Two studies have identified 2,4-pyridine-dicarboxylic acid (PDCA) as a small-molecule inhibitor of KDM5B (53,54). Following 24 h of OSKM overexpression, we observed a higher density and compaction of shKdm5b 4TF-MEFs than shLuc 4TF-MEFs (Fig.…”
Section: Kdm5b-depleted Es Cells Exhibit Reduced Self-renewalmentioning
confidence: 59%
“…S2 in the supplemental material). However, in contrast to all other small-molecule inhibitors used in this study, 2,4-PDCA, a histone demethylase inhibitor with high specificity for JARID1 and JMJD2 family demethylases, which are responsible for H3K4me3 and H3K36me3 demethylation, respectively (35), strongly enhanced both the direct repressive effect and stable silencing by antisense transcription during differentiation (Fig. 5E).…”
Section: Resultsmentioning
confidence: 99%
“…1a). Previously, we and others have shown that recombinant protein containing the N-terminal half of KDM5C (residues 1-839), KDM5B (residues 1-769), or KDM5A (residues 1-797) is enzymatically active (43)(44)(45). Interestingly, the rice Jumonji demethylase JMJ703 has KDM5-like activity on trimethylated histone H3 Lys-4 but contains no insertion within the catalytic domain (47).…”
Section: The Atomic Coordinates and Structure Factors (Code 5e6h) Havmentioning
confidence: 99%
“…1a), we generated a hypothetical structural model for the N-terminal half of the KDM5 family, which is enzymatically active in vitro (43,44), using PHYRE2 (Protein Homology/analogy Recognition Engine) (57). With PHYRE2, we generated individual domain models based on known structural information.…”
Section: A Hypothetical Model Of the N-terminal Half Of Kdm5-tomentioning
confidence: 99%